2012
DOI: 10.7243/2049-7962-1-15
|View full text |Cite
|
Sign up to set email alerts
|

Parotid Metastasis of Renal Cell Carcinoma: A Case Report and Review of the Literature

Abstract: Background: To review the presentation and management of renal cell carcinoma metastatic to the parotid gland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Epidemiological data show that cases in male patients predominated (2 : 1) in the published cases [14,46], reflecting the epidemiology of this malignancy [11,14,46], whereas in our series the reverse was observed (M : F = 1 : 2). The peak incidence occurs in the 7 th to 8 th decade.…”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations
“…Epidemiological data show that cases in male patients predominated (2 : 1) in the published cases [14,46], reflecting the epidemiology of this malignancy [11,14,46], whereas in our series the reverse was observed (M : F = 1 : 2). The peak incidence occurs in the 7 th to 8 th decade.…”
Section: Discussionsupporting
confidence: 43%
“…It is estimated that 30% of organ-confined RCCs will develop metastatic disease after local treatment [11]. Non-central nervous system (non-CNS) head and neck metastases from RCC are uncommon, comprising approximately 15% of tumors [12], but are not infrequently identified in the skin, nasal cavity, lips, hard palate, tongue, sinuses, and tonsils [6,10,13,14]. The thyroid gland is the most common site of head and neck metastasis for RCC [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first cases of parotid involvement due to RCC metastases were reported by Patey et al in 1965 7 . Since then, there have been limited reported cases of this phenomenon 6,[8][9][10][11][12][13][14][15][16] . In their review of the literature, Lawlor et al reported 45 cases of RCC metastasizing to the parotid, of which only 31 were complete case presentations 6 .…”
Section: Discussionmentioning
confidence: 99%
“…The RCC is recognized for its unique metastasis pattern owing to its ability to spread by mainly vascular, yet also lymphatic channels 5,6 . Well established sites for metastasis are bone, adrenals, lung and the contralateral kidney; however, metastasis to the head and neck is extremely rare 6 . We report a rare case of the CCRCC metastasizing to the parotid gland more than five years following nephrectomy.…”
Section: Introductionmentioning
confidence: 99%